2015
DOI: 10.1021/acs.biochem.5b00535
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/Deuterium Exchange and Molecular Dynamics Analysis of Amyloid Fibrils Formed by a D69K Charge-Pair Mutant of Human Apolipoprotein C-II

Abstract: Plasma apolipoproteins form amphipathic α helices in lipid environments but in the lipid-free state show a high propensity to form β structure and self-associate into amyloid fibrils. The widespread occurrence of apolipoproteins in amyloid plaques suggests disease-related roles, specifically in atherosclerosis. To reconcile the dual abilities of apolipoproteins to form either α helices or cross-β sheet structures, we examined fibrils formed by human apolipoprotein C-II (apoC-II). A structural model for apoC-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…In particular, electrostatic interactions, local hydrophobic contacts, and π stacking interfere with the well‐ordered core structure of Aβ fibrils, which is stabilized primarily by hydrogen bonds . Mutations can be introduced systematically along the entire peptide sequence, for example, by alanine or proline scans, or as point mutations introduced locally at structurally important intra‐ and interstrand contact points …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In particular, electrostatic interactions, local hydrophobic contacts, and π stacking interfere with the well‐ordered core structure of Aβ fibrils, which is stabilized primarily by hydrogen bonds . Mutations can be introduced systematically along the entire peptide sequence, for example, by alanine or proline scans, or as point mutations introduced locally at structurally important intra‐ and interstrand contact points …”
Section: Discussionmentioning
confidence: 66%
“…Each mutation introduces modified physical forces that alter the local interaction pattern, which in turn lead to specific differences in fibril structure and fibrillation kinetics. Thus, not only familial variants, but also rationally designed peptides carrying mutations that introduce specific interactions and/or perturbations are a useful tool to investigate the thermodynamics and kinetics of fibril formation as well as the fibril morphology, local structure, and dynamics, as demonstrated in several studies . Such rationally designed polypeptide sequences that can probe the influence of a local specific physical force may help to understand the underlying principles of fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both the meridional and equatorial spacings are different for the twisted‐ribbon and rod‐like fibrillar structures. The two longer equatorial spacings (23.8 and 46.6 Å) for rod‐like fibrils are not observed in X‐ray diffraction patterns for aligned twisted‐ribbon fibrils and suggest the presence of more than two β‐sheets in the fibril cross section.…”
Section: Resultsmentioning
confidence: 89%
“…[16][17][18][19][20] Researchers have shown that mutations introduced into lipid and lipoprotein lipase-binding portions of the Apo-CII protein can promote amyloid fibrillogenesis. [21][22][23] The E69V mutation discovered in this study is in the linker region, and isMD simulations suggest that the mutation can alter the conformation of the protein. Hence, it is possible that the E69V alteration mediates amyloid fibrillogenesis through destabilization of the mutant Apo-CII protein.…”
mentioning
confidence: 71%
“…This protein was previously shown to be amyloidogenic in animal models and in vitro studies. 16,17,[19][20][21][22][23] Thus, Apo-CII was considered a potential primary amyloid precursor protein in these cases.…”
Section: Concise Methodsmentioning
confidence: 99%